2023
DOI: 10.1002/marc.202300169
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Performance Stretchable Conjugated Polymers via Donor Structure Engineering

Abstract: A backbone engineering strategy is developed to tune the mechanical and electrical properties of conjugated polymer semiconductors. Four Donor–Acceptor (D–A) polymers, named PTDPPSe, PTDPPTT, PTDPPBT, and PTDPPTVT, are synthesized using selenophene (Se), thienothiophene (TT), bithiophene (BT), and thienylenevinylenethiophene (TVT) as the donors and siloxane side chain modified diketopyrrolopyrrole (DPP) as acceptor. The influences of the donor structure on the polymer energy level, film morphology, molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…18 With incorporation of the additives, the hole-carrier density decreased, but the crystallinity of the P3HT film increased; therefore, it was confirmed that there was no significant change in the field-effect mobility. 36 To examine the gas sensing performance, gas sensor devices employing the films were exposed to 10 ppm NO 2 for 20 s and repeatedly purged with air for 200 s. The drain current (I d ) was measured over time at a gate voltage (V G ) and drain voltage (V D ) of À10 V (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…18 With incorporation of the additives, the hole-carrier density decreased, but the crystallinity of the P3HT film increased; therefore, it was confirmed that there was no significant change in the field-effect mobility. 36 To examine the gas sensing performance, gas sensor devices employing the films were exposed to 10 ppm NO 2 for 20 s and repeatedly purged with air for 200 s. The drain current (I d ) was measured over time at a gate voltage (V G ) and drain voltage (V D ) of À10 V (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…[46,47] For PDPP/PCS blends, the alkyl spacing distance increases from 19.6 Å up to 20.0 Å and the 𝜋-𝜋 stacking distance increases from 3.72 up to 3.77 Å. [48,49] In the PBTTT/PCS and P3HT/PCS systems, the addition of PCS causes some of the conjugated polymer chains to align in the face on orientation. For PBTTT/PCS blends, the in-plane alkyl spacing distance ranges from 22.0 to 22.8 Å, which is close to the out-of-plane alkyl spacing distance.…”
Section: Resultsmentioning
confidence: 99%
“…By virtue of their light harvesting properties, CPEs have also been utilized as photosensitizers in fluorescent sensors [9] and solar cells applications [7][8][9][10]. The basis of such successful utilization of the CPEs in the optoelectronic applications is their chemical structures which can be easily changed as well as their semiconducting properties with large optical densities [11,12]. In addition, their high emission intensities can be also one of their important features to be used for fluorescence resonance energy transfer [13,14].…”
Section: Introductionmentioning
confidence: 99%